The Holistic Approach of Garbhsanskaar: A Narrative Review of its Practices and Benefits - Malik, Sweta; Singh, Rajesh; Sheetal (International Research Journal of Ayurveda & Yoga, 2024)
Introduction: Garbhsanskaar is an ancient Indian tradition or prenatal practice that encompasses a range of prenatal practices aimed at enhancing the mental, physical, emotional, and spiritual well-being of an unborn child. Rooted in Indian tradition, these practices include reading spiritual books, chanting mantrs, meditation, yoga, dietary regulations, listening to music, and engaging in creative, positive, and spiritually enriching activities. Methods: Literature from a range of sources including ancient texts, contemporary research articles, and clinical studies was conducted for this study. Furthermore, databases such as Google Scholar, PubMed, and traditional Ayurvedic manuscripts till December 2023 were utilized to gather relevant information on Garbhsanskaar practices and its effects. Results: Numerous researches on Garbhsanskaar or prenatal care and its effects on expectant mothers and their unborn children revealed several kinds of advantages for their physical, emotional, and spiritual well-being. These exercises include yoga, meditation, pranayama, yoga nidra, diet, painting, and reading sacred texts. Discussion: This study presents that all the practices which come under the Garbhsanskaar ritual actually improve the mother’s and the baby’s physical, mental, and spiritual well-being. Conclusion: Garbhsanskaar offers a valuable perspective on prenatal care and should become essential in the life of pregnant women. Garbhsanskaar is an ancient Indian practice that involves a series of traditional rituals during pregnancy. This Sanskar aimed to uplift the mental, physical, emotional, and spiritual well-being of an unborn child. The term “Garbhsanskaar” is derived from two Sanskrit words, where “Garbha,” meaning womb of a mother, and “Sanskaar,” meaning education/values.[1,2] The Vedas and Puranas are ancient Indian books that have references about the Garbhsanskaar practice. It is widely believed that a baby’s physical, mental, and spiritual development starts in the womb and the unborn child is greatly influenced by the mother’s thoughts, feelings, and surroundings. Historical figures, such